2018
DOI: 10.1093/annonc/mdy511.005
|View full text |Cite
|
Sign up to set email alerts
|

Durvalumab with or without tremelimumab vs platinum-based chemotherapy as first-line treatment for metastatic non-small cell lung cancer: MYSTIC

Abstract: Background: PD1 inhibitors as well as PD1/CTLA4 combinations have shown remarkable efficacy in the first-line treatment of metastatic melanoma. The impact of many concomitant medications on the clinical outcomes from PD1 based therapies remains elusive. Methods: We retrospectively analyzed 140 patients included in the Checkmate 069 phase II clinical trial as a discovery cohort, comparing ipilimumab monotherapy with ipilimumab combined with nivolumab. We compared response rates, progression-free survival and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 0 publications
5
113
0
2
Order By: Relevance
“…The phase III MYSTIC trial of first-line durvalumab monotherapy or durvalumab þ tremelimumab versus standard of care chemotherapy did not show a statistically significant PFS or OS advantage for either arm in patients with greater than or equal to 25% PD-L1 expression; however, durvalumab showed a clinically meaningful improvement in OS compared to chemotherapy (hazard ratio ¼ 0.76, 97.54% CI: 0.564-1.019; p ¼ 0.036). 36 The phase III PACIFIC trial of durvalumab following concurrent chemoradiotherapy in stage III, unresectable NSCLC showed statistically significant improvements in PFS and OS over placebo leading to registration for this indication. 15,37…”
Section: Discussionmentioning
confidence: 99%
“…The phase III MYSTIC trial of first-line durvalumab monotherapy or durvalumab þ tremelimumab versus standard of care chemotherapy did not show a statistically significant PFS or OS advantage for either arm in patients with greater than or equal to 25% PD-L1 expression; however, durvalumab showed a clinically meaningful improvement in OS compared to chemotherapy (hazard ratio ¼ 0.76, 97.54% CI: 0.564-1.019; p ¼ 0.036). 36 The phase III PACIFIC trial of durvalumab following concurrent chemoradiotherapy in stage III, unresectable NSCLC showed statistically significant improvements in PFS and OS over placebo leading to registration for this indication. 15,37…”
Section: Discussionmentioning
confidence: 99%
“…IO targets immune pathways allowing the body to recognize cancer cells as foreign and attack them (e.g., immune checkpoint inhibitors) or enhance overall immune functioning without targeting specific cancer cells (e.g., interleukins, interferons). When administered as monotherapy for treating advanced NSCLC, IO has been associated with response rates of approximately 20% in previously treated patients [4][5][6][7][8] and more than 25% in those who are treatment naive [9][10][11][12]. Compared with conventional chemotherapy, IO has been shown to have a comparatively benign safety profile, though the management of immune-related adverse events, which are frequently grades 1-2 but can affect multiple organ systems, is a prevalent concern [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in detail in a subsequent section, the utility of TMB as a clinically meaningful biomarker for PD-1/CTLA-4 combination immunotherapy was demonstrated by primary results from CheckMate 227 part 1, which showed that the study met the coprimary end point of significantly longer PFS with nivolumab plus ipilimumab versus chemotherapy in patients with TMB ≥10 mutations/Mb [47]. Although the Phase III MYSTIC study failed to show a significant OS advantage with first-line durvalumab plus tremelimumab versus chemotherapy in patients with ≥25% PD-L1 expression (coprimary end point), recent results of an exploratory analysis showed improved OS with the combination therapy versus chemotherapy in patients with a blood TMB ≥16 mutations/Mb (HR: 0.62; 95% CI: 0.45-0.86) [48].…”
Section: First-line Treatmentmentioning
confidence: 99%
“…A current limitation in comparing TMB-related outcomes across studies in NSCLC is the lack of a universally adopted standard for the definition and determination of TMB. Both whole-exome sequencing (WES) [38,39,46] and next-generation sequencing using specific gene panels [47,48] have been used to determine TMB expressed as mutations per whole exome or mutations per megabase, respectively. In addition, the type of mutations included for the determination of TMB may vary between studies.…”
Section: Clinical Efficacy Of First-line Nivolumab Plus Ipilimumabmentioning
confidence: 99%
See 1 more Smart Citation